2018
DOI: 10.11118/actaun201866030791
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors for Start-ups Related to Agriculture, Food and Nutrition and Their Relevance to Education

Abstract: Continuous formation of new businesses, start-ups, which could establish themselves on the market and be successful, should be supported in all economic areas, and the area of agriculture is no exception. Thus the main aim of this paper is to formulate a recommendation for educational institutions which prepare future generations, among others, to establish start-ups in agriculture that reflect fundamental success factors. The data were acquired with the aid of structured interviews (n = 6), which were carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The findings of this study are supported by the opinion of Sarasvathy and Menon (2013) when noted that experiences possessed by the entrepreneurs are a determinant of success or failure of the firms due to the fact that knowledge acquired by the entrepreneurs in their previous business ventures plays a significant impact in their future decisions. The findings are also in line with the findings of Smolová, Kubová, and Urbancová (2018) who identified experience as a success factor of start-ups related to the agriculture, food and nutrition sector of the economy.…”
Section: Discussion Of Major Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of this study are supported by the opinion of Sarasvathy and Menon (2013) when noted that experiences possessed by the entrepreneurs are a determinant of success or failure of the firms due to the fact that knowledge acquired by the entrepreneurs in their previous business ventures plays a significant impact in their future decisions. The findings are also in line with the findings of Smolová, Kubová, and Urbancová (2018) who identified experience as a success factor of start-ups related to the agriculture, food and nutrition sector of the economy.…”
Section: Discussion Of Major Findingssupporting
confidence: 89%
“…The present findings are supported by the findings of Simon and Watson (2014) when they revealed that entrepreneurial intention measured by attitude has a positive impact on the business performance of small, medium scale enterprises. The findings are also supported by the discovery of Smolová, Kubová, and Urbancová (2018) when they found that positive attitudes towards business and experience are success factors of start-ups.…”
Section: Discussion Of Major Findingsmentioning
confidence: 68%
“…For example, research in Korea addressing the performance of manufacturing SMEs show highlighted the relevance of Government Assistance Programs to improving start-up and SMEs performances [33]. The results in the Czech Republic show that key success criteria (p-value = 0.000) of successful start-ups are: use of education and training, development, partners, theoretical mapping, use of expert help, use of concrete technologies, knowledge of project management, project functionality, personal interest in project delivery, and efficiency of solutions [23], which are in accordance with reference [25].…”
supporting
confidence: 69%
“…We can suggest that educational and other institutions which focus on the support of start-ups project should focus on courses in the area of increasing the efficiency of a manager's work through correct planning, effective time usage, and development of the competencies of their teams through delegation. It is necessary to focus on the problem of self-management and life-management, which would contribute to the prevention of burnout and workaholic syndromes, and towards building a healthy lifestyle, which was confirmed by reference [25].…”
mentioning
confidence: 90%
See 1 more Smart Citation